Variação e gramaticalização no uso de preposições em contextos de verbos de movimento no português brasileiro - Wiedemer, Marcos Luiz [UNESP] (2013)
The objective of this thesis is to investigate the variation and change of prepositions, involving prepositions a/para/em introducing locative complement of motion verbs (caminhar (walk), chegar (arrive), entrar (come in), ir (go), levar (take), mudar (move), partir (leave), sair (go out), voltar (come back)) through grammaticalization. Therefore, this investigation is supported by framework of Grammaticalization (HOPPER, 1991, HOPPER; TRAUGOTT, 1993, LEHMANN, 2002) and Sociolinguistics (WEINREICH; LABOV; HERZOG, 1968, LABOV, 1972, 1978, 2001). Aiming to combine present and past in search of dynamic and fluid relations between form and function, we investigated samples of Brazilian Portuguese from two synchronies: speech sample of XXI century extracted from samples of spoken Portuguese in the northwestern area of São Paulo state (Linguistic Sample from São Paulo State Project: GONÇALVES, 2007, 2008a, 2008b), and writing sample of XIX century, constituted by written texts. The objective is to reconstitute clines of changing occurred in the contexts of motion verbs in Brazilian Portuguese. The results demonstrate that these prepositions designate exclusively space notions, and the location notions is provided by the semantic and syntactic valency of the verb. The differences of meaning which update the prepositions are derived from a regular relationship between basic meaning and generic meaning, and the gradual increase of pragmatization (inference) and abstractization (metaphoric strategies) of meaning in the use of these prepositions. In contemporary Portuguese, we found the process of stable variation of the prepositions 'em' and 'para' with greater meaning abstractization, which explains the inclusion of new types of complements and the influence of social and linguistic factors in the selection of a specific preposition, and a process of decline the gradual preposition 'a'. Furthermore, we showed that there is a process of ...